Fácies, sistemas deposicionais, quimioestratigrafia e estratigrafia de sequências da Formação Sete Lagoas na região de Januária, norte do estado de Minas Gerais - Pascoal Perrella Junior (2016)
The Januária Sheet (Minas Gerais, Brazil) presents two geological domains separated by the São Francisco River. Sedimentary rocks of the Sete Lagoas Formation are exposed in the left margin of the river, composing a succession deposited on the Januária basement high, and unconformably overlain by lithologies of the Urucuia Group. Sedimentary rocks of the Serra de Santa Helena, Lagoa do Jacaré and Serra da Saudade compound the right side domain. The rocks of Sete Lagoas Formation show both lateral and vertical rock stacking along continuous outcrops, witch conjugated to well-preserved primary structures and textures, allowed detailed facies analysis and sequence stratigraphy studies. These studies also integrate data from geological mapping, microcroscopic petrography and high-resolution C and O isotope analysis from three stratigraphic sections. Eight facies and four facies associations make up a second order sequence composed by a transgressive system tract in the base, and a high stand system tract in the upper portion, separated by a maximum flooding surface. The transgressive system tract comprises the outer platform, whilst the high stand system tract encompasses the inner platform, shoreface, and intertidal/supratidal facies association. The outer platform association encompasses dolomites, hybrid stromatolites and argillaceous stratiform stromatolites. The inner platform association is characterized by grainstones with hummocky cross stratification and thrombolithic intercalations. The shoreface association presents grainstones with ripple marks and oolithic lenses, intercalated with thrombolitic laminas locally bearing Cloudina fossils. The intertidal/supratidal association comprises intercalations of flat-pebble rudstones and flat laminites. The high stand system tract shows a progradation stacking from the basement high apex towards progressively deeper basement areas. This stratigraphic framework associated with stratigraphic and isotopic features indicate that the now exposed Januária basement high also represents a paleo-high during the sedimentation event. Aragonite pseudomorphs coupled with 13C values of -5 characterize the basal carbonate of the Sete Lagoas Formation as a cap carbonate at the base of the transgressive tract. Records of the Cloudina fossil, recognized in the high stand tract, indicate a Late Ediacaran age for this upper portion of studied stratigraphic sequence.